Pelaksanaan Pengelolaan Aset Desa - Reni Wahyuni (Jurnal El-Thawalib, 2022)
This study discusses the implementation of the Minister of Home Affairs Regulation No. 1 of 2016 concerning Management of Village Assets in Attitude Village, Muara Batang Gadis District, Mandailing Natal Regency. This research is motivated by the complaints of the village community of Attitudes about the Management of Village Assets sourced from the Company PT. Madina Agro Lestari yields from 10 hectares of core land or CSR (Corporate Social Responsibility) are not distributed as mutually agreed upon in the Realization of the Attitude Village Cash Garden, therefore the people of Attitude Village request that the company temporarily stop the results from the core land or CSR ( Corporate Social Responsibility) is caused by the distribution to the village government from the previous three years cannot be accounted for by the Village Head. This type of research is a field research using a qualitative descriptive analysis method. The method of collecting data in this research is by interview and documentation in accordance with the provisions contained in the Regulation of the Minister of Home Affairs No.1 of 2016 concerning Management of Village Assets in Attitude Village, Muara Batang Gadis District, Mandailing Natal Regency, which is related to the Implementation of the Ministerial Regulation Domestic Affairs No.1 of 2016 concerning Village Asset Management. The parties interviewed were the Head of Attitude Village, Manager of PT. Madina Agro Lestari, and the village community of Attitudes. The results of the study stated that the implementation of the Minister of Home Affairs Regulation No. 1 of 2016 concerning Management of Village Assets in Attitude Village, Muara Batang Gadis District, Mandailing Natal Regency had not been carried out properly, this can be seen from the form of implementation that has been determined by the Village Head, namely by carrying out market development traditional development that can create community economic growth, the construction of a soccer field gate is one of the developments that has not been carried out properly and, development in the field of education due to the absence of land acquisition to build schools from the junior and senior high school levels, besides that the government is also less trying to find solutions to this problem.